Who cares about the carers? A call to action on behalf of mothers of disabled children - Pearson, Alison (Frontiers in Sociology, 2024)
This ‘perspective’ article is an urgent call to action on behalf of mothers (and indeed fathers) of disabled children in the wake of the COVID-19 pandemic. In doing so draws attention to the ‘perfect storm’ experienced by United Kingdom-based parents of reduced support and increased stress, coupled with the effects of isolation. It also illuminates some of the impact of actions taken, and not taken, during and after the pandemic and the enduring effects for working parent-carers. In doing so I argue that, despite facing these extreme challenges, these parents have been a neglected group from both a policy and research perspective. The call to action therefore extends to society, employers, and to the research community.